DISCOURSE ON NUTRITION SERVICE FACILITIES POLICY IN SUPPORTING THE FREE NUTRITIONAL MEAL POLICY IN PRISONS AND DETENTION CENTERS - Ibnu Arif Risyat; Muhadam Labolo; Alma’arif (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
The Free Nutritious Meal (MBG) Program represents a strategic government initiative designed to improve the nutritional status of schoolchildren, pregnant women, breastfeeding mothers, and toddlers in Indonesia. One of its innovative policy approaches involves utilizing correctional institution kitchens as Nutritional Fulfillment Service Units (SPPG), while engaging inmates as operational personnel through correctional self-reliance programs. This study aims to examine the policy discourse surrounding the utilization of prison-based SPPGs in supporting the implementation of the MBG Program. Employing a qualitative research design, the study adopts a discourse analysis approach based on documentary analysis of government regulations, policy documents, scholarly publications, mass media reports, and social media content. The findings reveal two dominant and competing policy narratives. The supportive discourse emphasizes the optimization of public assets, greater implementation efficiency, and the socioeconomic empowerment of inmates through productive participation. In contrast, the critical discourse raises concerns regarding governance quality, budget transparency, food safety and security, implementation standards, and institutional accountability. Overall, the study concludes that the successful integration of prison-based SPPGs into the MBG Program depends on adequate infrastructure, effective inter-agency coordination, transparent and accountable governance, and robust monitoring and evaluation mechanisms to ensure the program's legitimacy, effectiveness, and long-term sustainability.